2016
DOI: 10.14236/ewic/hci2016.70
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on the Design of Smart Homes for People with Dementia Using a User-Centred Design Approach

Abstract: The number of people with dementia is rising every year, and it is getting more expensive to provide care for them in specially designed care centres. Furthermore, some people with dementia prefer to live independently, and to be accompanied by informal and family caregivers. One way to meet this requirement of people with dementia is to place them in smart homes. Smart homes facilitate extra care for people with dementia with automated and semi-automated support. However, smart homes need to be designed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…Our results were similar to those of previous reviews, where smart home technology was used to build up a picture of how they could provide an illness‐centred approach (Raei & Bouchachia, ) and how effective the technology was with regard to helping older people feel safe and independent at home (Morris et al, ; Peetom et al, ). However, the world we live in, and the way we care for older people, is constantly changing and new smart home technology is being developed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results were similar to those of previous reviews, where smart home technology was used to build up a picture of how they could provide an illness‐centred approach (Raei & Bouchachia, ) and how effective the technology was with regard to helping older people feel safe and independent at home (Morris et al, ; Peetom et al, ). However, the world we live in, and the way we care for older people, is constantly changing and new smart home technology is being developed.…”
Section: Discussionsupporting
confidence: 89%
“…Our review shows that smart homes supported older people's daily activities and healthy living, by improving the quality of their daily activities, tasks and how they used objects in everyday life (Morris et al, , Peetom et al, , Raei & Bouchachia, ), as reported in the previous studies. They also improved their ability to cope.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, our findings also reinforce the importance of including measures of user perceptions and acceptance within evaluation studies (as was done in three studies), as these factors are known important drivers in smart home technology usage and, ultimately, effectiveness [31]. Echoing the recommendations of previous authors [10,32], we therefore also encourage that future studies aim to include the experiences and preferences of end-users (e.g., people with dementia and their carers) explicitly in the development and evaluations of the smart home technologies.…”
Section: Discussionsupporting
confidence: 78%
“…For example, a smart home could provide a dementia-friendly design and include technologies to facilitate extra care with (semi-)automated support [3]. Other assistive environments could focus, for example, on frailty or other physical or sensory disabilities.…”
Section: Introductionmentioning
confidence: 99%